Ứng dụng phương pháp thành phần đối xứng trong nghiên cứu các hệ hai kênh - Châu, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2016)
In this paper the Duality Approach is  applied to find out the weight functions of two-input two-output systems.